AAMP98 カンソク キカン チュウ ノ レーダー カンソク - 小西, 啓之; コニシ, ヒロユキ; 和田, 誠; ワダ, マコト; 塩原, 匡貴; シオバラ, マサタカ; Konishi, Hiroyuki; Wada, Makoto; Shiobara, Masataka (2002)
P(論文) AAMP期間中を含む1997年12月 から1998年3月のNy-Alesundの冬季の雲の特徴をレーダーエコーから分類した．その結果，降水エコー出現頻度は，気温の高低とよく対応し，気温が高くなると降水エコーの出現頻度は，50%近くになった． 観測期間平均の降水エコー出現頻度は23%であった． また，降水エコーが層状性であるか対流性であるかを調べた結果，層状性の降水エコーが全体の64%を占めた． この割合は，気温が低下すると大きくなり，平均気温 が－20℃より低かった2月には，80%を越えた． AAMP期間中は，マイクロパルスライダー（MPL）による雲エコーとの比較も行った． レーダーによる降水エコーの出現頻度は15% と少なかったが，雲エコーの出現頻度は70%もあり，降水域と雲域に大きな差があることが示唆された． Precipitation clouds were classified by vertical pointing radar data measured at Ny-Alesund, Arctic from December 1997 to March 1998 including the AAMP period. The results show that the apparent radar echo frequency averaged 23% over the period and increased to roughly 50% in a warmer period. The ratio of apparent time between layer and convective clouds was 64% to 36%. The propotion of layer clouds increased in the colder period and exceeded 80% in February when the averaged temperature at the ground was lower than - 20°C. The radar echo data were also compared with Micro-pulse Lidar (MPL) data during the AAMP period. The apparent MPL echo frequency reached 70%; on the other hand, that of the radar echo was 15%. The results suggest that the area of clouds was much larger than that of precipitation. departmental bulletin paper